Lessons from COVID-19 for behavioural and communication interventions to enhance vaccine uptake - Lewandowsky S; Schmid P; Habersaat KB; Nielsen SM; Seale H; Betsch C; Böhm R; Geiger M; Craig B; Sunstein C; Sah S; MacDonald NE; et al. (Springer Nature Limited, 2023)
The Covid pandemic has yielded new insights into psychological vaccine acceptance factors. This knowledge serves as a basis for behavioral and communication interventions that can increase vaccination readiness for other diseases.